Needs Analysis on English Language Use in Tour Guiding: Penelitian - Mella Narolita; Aulia Restu Ariyanto Putri (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to identify the need for English in guiding activities in Bedono Tourism Village, Demak Regency. This study used a quantitative descriptive method with respondents who are members of the Bedono community-based tourism group. The results of the study indicate that members of community-based tourism group have a high awareness of the importance of English skills, especially in the context of direct communication with foreign tourists. Speaking skills are the main focus needed, accompanied by training materials that are contextual and relevant to local conditions, such as tourism vocabulary, local culture, and tourism-related information. Although some members have experience in English and have participated in training, the use of English is not evenly distributed and has not become a habit. The main obstacles faced include limited vocabulary and minimal opportunities for practice. Therefore, training methods that are direct practice, such as roleplay and simulation, are considered the most appropriate. The results of the study also show that there is hope for support from both the government and related institutions for the sustainability of the program. Based on the results of the study, it is recommended to develop training based on local needs, interactive and applicable learning designs, and cross-sector collaboration to improve the professionalism of members of community-based tourism groups.